Delivery at term: when, how and why - Walker, Kate F.; Thornton, Jim (Elsevier, 2018)
The optimal timing of delivery for the baby is 39 weeks, avoiding the morbidity associated with early term birth and reducing the risk of antepartum stillbirth.